Co-creative Innovation Labs as Alternative Enablers of Corporate Innovation - Bouthouri, Annina (My University, 2020)
Today’s companies have understood the meaning of the mantra “innovate or die” and innovation is seen as the most important resource for achieving and maintaining a competitive advantage. Pioneering companies have succeeded to turn emerging technologies in their favor and produced completely new innovative products and services that have transformed the company's position into a monopoly. As innovation leaders benefit from the original monopoly situation, it has attracted other companies to get excited about different innovation efforts, such as innovation labs. Innovation labs are new types of organizational spaces that provide a more results and agile oriented solution to the ever-changing customer requirements and high uncertainties that companies currently face. Innovation labs aim to stimulate the creativity of their participants and facilitate the development of innovative business models, products and services, either onsite or offsite the company. These collaborative workspaces unite creative talents and experts in various fields to explore and extend their creative thinking above usual boundaries. This case study explores how innovation labs intersect with corporation’s innovation management efforts. With the help of 15 interviewees, it provides the latest information on the attitudes and views of Finnish corporations towards innovation labs. In addition, this research offers readers a digital innovation management best practices model which brings together practices from various scientific literature journals. One of the main findings of the research was the fact that the majority of the interviewed companies already followed presented best practices model.
Keywords: Innovation Lab, Digital Innovation Management, Innovation Space, Co-Creation Space, Digital Innovation, Corporate Innovation